The Effect of Health Education with “Buharti” Package Media (High Risk Pregnant Women Booklet) on Pregnant Women's Readiness in Facing Labor - Prihatin, Eny Septi Wulandari Dwi; Pratiwi, Etik (Jurnal Penelitian Perawat Profesional, 2025)
High-risk pregnancy is a pregnancy process that has a higher and greater risk than normal pregnancy in general. Health education for pregnant women with high risk is very important to be given in perinatal care. The purpose of this study was to determine the effect of health education with the Bu harti package media (Booklet for High-Risk Pregnant Women) on the readiness of pregnant women in facing childbirth. The specific purpose of this study was to identify the characteristics of high-risk pregnant women. This type of research is a quantitative study with a quasi-experimental design using a quasi-experimental research design. The sampling technique was purposive sampling, namely pregnant women with high risk who visited the Imogiri I Health Center as many as 60 people. The research instruments used were the Demographic Data questionnaire, and the Birth Preparedness and Complication Readiness (BPCR) questionnaire regarding childbirth readiness. The media used to provide health education was the high-risk pregnant women booklet package. The results showed that there was a significant influence on health education media booklet package for high-risk pregnant women “Bu Harti” with the readiness of pregnant women to face childbirth (Significance 0.001 <0.0005). The conclusion of this study is that there is a significant influence of providing education using the “Bu Harti” package on childbirth readiness at Puskesmas Imogiri I.